PENGARUH PENGGUNAAN MEDIA KARTU PINTAR TERHADAP HASIL BELAJAR SISWA KELAS III DI MIN 2 PALEMBANG - Dwi Amanda, Valya; Middya Boty; Agra Dwi Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Inappropriate learning media makes it difficult for students to obtain good learning results. So, teachers must better understand and apply more varied learning media. This research aims to determine the effect of using smart card media on learning outcomes in Indonesian language subjects in class III MIN 2 Palembang. The research method carried out in this research uses a quantitative approach with the type of Quasi-Experimental Research or quasi-experimental research as well as a Nonequivalent Control Group Design research design. The samples in this study were students in class III G as the experimental class with a total of 28 students and class III D as the control class with a total of 27 students. The data analysis techniques used are normality test, homogeneity test, and hypothesis test. Data validity testing is carried out by testing data validity and reliability testing. The results of this research indicate that the application of smart card media to student learning outcomes in Indonesian language subjects is classified as very good. The experimental class obtained an average of 86.78 while the control class obtained an average of 80. The learning outcomes of the experimental class that applied smart card media were higher than the control class that did not apply smart card media. The results of research and data analysis obtained a significant value, namely 0.013 < 0.05, which means Ho is rejected and Ha is accepted. Based on the research results, it can be concluded that there is an influence of smart card media on student learning outcomes.